Functional Variable Method for the Nonlinear Fractional Differential Equations - Bekir, Ahmet; Guner, Ozkan; Aksoy, Esin; Pandir, Yusuf (AMER INST PHYSICS, 2015)
In this type functional variable method has been used to private type of nonlinear fractional differential equations. The main property of the method demonstrate in its flexibility and ability to solve nonlinear equations accurately, efficiency and conveniently. The fractional derivatives are described in the modified Riemann-Liouville sense. Three examples, are presented to show the application of the present technique. As a result, periodic and hyperbolic solutions are obtained.
Keywords: The functional variable method; Fractional differential equation; modified Riemann-Liouville derivative; Symbolic computation; FINDING EXACT-SOLUTIONS; 1ST INTEGRAL METHOD; COMPLEX TRANSFORM; Mathematics; Physics